2001
DOI: 10.1021/om010126k
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Bis(imino)pyridyl−Fe(II) Olefin Poly- and Oligomerization Catalysts. Dominance of Different Spin States in Propagation and β-Hydride Transfer Pathways

Abstract: Mechanisms of chain propagation and β-hydride transfer (BHT) chain termination stages of poly- and oligomerization of ethylene by catalysts of general formula [2,6-(CR1N((2-R2)(4-R4)(6-R3)C6H2)2C5H3N]FeCl2 were studied theoretically. Density functional (B3LYP) and integrated molecular orbitals + molecular mechanics (IMOMM) methods were applied respectively to a model (“low steric bulk”, LSB) system, [2,6-(CHNH)2C5H3N]FeCH3 +, and one of the catalytic (“high steric bulk”, HSB) systems studied experimentally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 78 publications
4
82
0
Order By: Relevance
“…It has also been shown by MO/MM studies that the steric effect of bulky ligands lowers this activation barrier. [67,72,79,81] Therefore, the calculations are consistent with [CpMo(h 4 -C 4 H 6 )R] being a good model for one of the catalytically active sites for our 2/MAO system. As is generally found, the relative stability of the agostic propyl product goes as b ) a b g. The parameters in Table 4 reveal that this trend parallels the strength of the agostic interaction (a greater stabilization is associated with shorter MoÀH and longer CÀH distances for the agostic H atom).…”
Section: Computational Studiessupporting
confidence: 82%
See 1 more Smart Citation
“…It has also been shown by MO/MM studies that the steric effect of bulky ligands lowers this activation barrier. [67,72,79,81] Therefore, the calculations are consistent with [CpMo(h 4 -C 4 H 6 )R] being a good model for one of the catalytically active sites for our 2/MAO system. As is generally found, the relative stability of the agostic propyl product goes as b ) a b g. The parameters in Table 4 reveal that this trend parallels the strength of the agostic interaction (a greater stabilization is associated with shorter MoÀH and longer CÀH distances for the agostic H atom).…”
Section: Computational Studiessupporting
confidence: 82%
“…[77,78] Theoretical calculations on the Brookhart/ Gibson catalysts also indicate the possible involvement of more than one spin state along the olefin polymerization process. [72,79] Therefore, we have extended our study to both spin doublet and quartet hypersurfaces for the Mo system, including the MECP.…”
Section: Computational Studiesmentioning
confidence: 99%
“…The calculations for the two extremes of steric bulk are in agreement with the observed suppression of β -hydride transfer termination upon increasing the steric bulk of the ligand l . For cobalt(I) alkyl Polymer complexes, experiment and theory have been shown to be in agreement and support a stepwise pathway for the reaction of the alkyl complexes with 1-alkenes, reacting by b -hydride transfer via a cobalt hydride intermediate [115] . Such cobalt alkyls have also been shown to contain low-spin cobalt(II) antiferromagnetically coupled to a ligand radical anion.…”
Section: Propagation and Chain Transfer Pathways/theoretical Studiesmentioning
confidence: 68%
“…Musaev, Morokuma and co-workers have been concerned with understanding the mechanisms of chain propagation and b -hydride transfer termination for a series of iron catalysts [115] . By varying the steric bulk of the systems studied, it was found that two axial ligands are required in order for the d z2 orbital to be destabilised (with the tridentate bis(imino)pyridine ligand defining the equatorial xy plane) and for the singlet to be the ground state, a situation found for the b -hydride termination species.…”
Section: Propagation and Chain Transfer Pathways/theoretical Studiesmentioning
confidence: 99%
“…5. The active species of the polymerization is initially considered to be cationic alkyl metal species, similar to the metallocene polymerization [178,179]. Detailed characterization of the active species and theoretical studies, however, clarified unique polymerization mechanism.…”
Section: Polymerization Of Olefins By Fe and Co Complexesmentioning
confidence: 99%